2009
DOI: 10.1375/prp.3.2.55
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Resilience in a Hakka Community in Taiwan

Abstract: Survivors of the 921 Earthquake in the Tung Shih areas were the target population for this study. The researchers used purposive sampling strategies to select information-rich participants for study in depth. A total of 15 interviewees and 8 focus group members participated in this study. Qualitative data analysis software, ATLAS.ti 5.5, was used for cross-case and content analyses. The results indicate that acceptance, preparedness, self-reliance, spirituality, Hakka spirit, resource availability, social supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…Filipinos, health and mental health decisions are made within the family (Nadal, 2011). Spirituality has also been identified as an important resilience factor among Asians (Jang & Wang, 2009;Hechanova et al, 2015).). Another cultural adaptation of both interventions was the use of groups.…”
Section: Designing and Implementing Community-based Mental Health Intmentioning
confidence: 99%
“…Filipinos, health and mental health decisions are made within the family (Nadal, 2011). Spirituality has also been identified as an important resilience factor among Asians (Jang & Wang, 2009;Hechanova et al, 2015).). Another cultural adaptation of both interventions was the use of groups.…”
Section: Designing and Implementing Community-based Mental Health Intmentioning
confidence: 99%
“…Findings from previous studies have suggested that a community's disaster resilience can be attributed to a variety of factors: a sense of community; problem-focused coping style; self-or collective efficacy (Tobin 1999;Paton and Johnston 2001) social support or social capital (Buckland and Rahman 1999;Buckle et al 2003;Rhinard and Sundelius 2010) citizen participation in voluntary organizations (Childs 2008) local leaders (Buckle et al 2003;Paton and Auld 2006;Boin 2010) disaster management policies, plans, and practices (Manyena 2006) process-oriented hazard mitigation policies (Birkland 2010) organizational preparedness (Kendra and Wachtendorf 2003) cooperation (Rhinard and Sundelius 2010) learning and communication (Buckle et al 2003;Comfort et al 2010) local knowledge, experience, value, and culture (Jang and LaMendola 2006;Jang and Wang 2009) infrastructure and lifelines (Cutter et al 2008(Cutter et al , 2010Johnston et al 2006) and the demographic characteristics of a community (Cutter et al 2008;Lahad 2008).…”
Section: Factors Affecting Disaster Resiliencementioning
confidence: 99%
“…Community-level factors include community culture, resource availability, social support, and an orientation to serving. Community cultural characteristics associated with resilience are frugality, diligence, self-reliance, responsibility, and persistence (Jang & Wang, 2009). …”
Section: Resilience Interventionsmentioning
confidence: 99%
“…On the other hand, community resilience (sense of community, collective self-efficacy, articulation of problems, social support, availability of physical and emotional resources) helps people prepare for and cope with disasters. Finally, societal institutions and the resources they provide influence psychological, family, and community resilience.The importance of both internal and external resilience factors was affirmed in a study among Taiwan disaster survivors (Jang & Wang, 2009). Results reveal that personal resilience factors included acceptance, preparedness, self-reliance, and spirituality.…”
mentioning
confidence: 92%